Indigenous Knowledge and Resource Management: Concerns of Indian Scheduled Tribes and Community-centered Initiatives - Jha, Amaresh; Vats, Aman (Journal of Advanced Research in Humanities and Social Sciences, 2021)
Indigenous resources primarily comprise Indigenous Peoples, and Indigenous Knowledge is a set of their culture, beliefs and practices. Unfortunately the indigenous resource management in India primarily focuses on management of natural resources- forest produces, mines and minerals, rivers and water bodies to fulfil the need of the 91% non-tribal population and is least concerned about community-grounded practices for holistic development of the Scheduled Tribes in their own cultural ecosystem. Lack of integration of tangible and intangible resources while preserving the cultural heritage of Tribes has led to creation of non-living archives of living Indigenous Peoples. The Intellectual Property Rights of the Indigenous Knowledge is another concern which has largely remained unaddressed. This study brings into account the concerns of the locals who own the Indigenous Knowledge and the global practices of community based preservation of Indigenous. The study concludes that the capacity building of communities for preservation of their own knowledge in their own socio-cultural settings is the most sustainable solution. How to cite this article:  Jha A, Vats A. Indigenous Knowledge and Resource Management: Concerns of Indian Scheduled Tribes and Community-centered Initiatives. J Adv Res Humani Social Sci 2021; 8(3): 1-7. DOI:  https://doi.org/10.24321/2349.2872.202102